The Autophagy-Initiating Kinase ULK1 Controls RIPK1-Mediated Cell Death - Wenxian Wu; Xiaojing Wang; Niklas Berleth; Jana Deitersen; Nora Wallot-Hieke; Philip Böhler; David Schlütermann; Fabian Stuhldreier; Jan Cox; Katharina Schmitz; Sabine Seggewiß; Christoph Peter; et al. (Cell Reports, 2020)
Summary: Autophagy, apoptosis, and necroptosis are stress responses governing the ultimate fate of a cell. However, the crosstalk between these cellular stress responses is not entirely understood. Especially, it is not clear whether the autophagy-initiating kinase ULK1 and the cell-death-regulating kinase RIPK1 are involved in this potential crosstalk. Here, we identify RIPK1 as a substrate of ULK1. ULK1-dependent phosphorylation of RIPK1 reduces complex IIb/necrosome assembly and tumor necrosis factor (TNF)-induced cell death, whereas deprivation of ULK1 enhances TNF-induced cell death. We observe that ULK1 phosphorylates multiple sites of RIPK1, but it appears that especially phosphorylation of S357 within the intermediate domain of RIPK1 mediates this cell-death-inhibiting effect. We propose that ULK1 is a regulator of RIPK1-mediated cell death. : Wu et al. show that the autophagy-inducing kinase ULK1 phosphorylates the necroptosis-regulating kinase RIPK1 within its intermediate domain at Ser357. This phosphorylation reduces the assembly of the death-inducing complex IIb/necrosome and, thus, TNF-induced cell death. Keywords: ULK1, RIPK1, RIPK3, autophagy, necroptosis, TNF, MLKL, necrosome, complex I, complex II